O jornalismo de entretenimento como objeto de estudo nas matrizes de jornalismo e rádio-TV-internet e sua produção na prática - Marchetti, Paulo (2024)
This dissertation is a reflection on the change that has taken place in the journalism profession, its new purpose, and the extent to which this change needs to be rethought in the academic sphere. To this end, the curriculum of the Journalism and Radio-TV-Internet courses at private and public universities were analyzed because of the similarities between the two professions, their activities and working tools. Through professional experience, diverse research and practical examples, the dissertation discusses the creation of a new academic activity called Entertainment Journalism, the result of combining the two courses analyzed. There are two fronts of study: theory and practice within the curriculum and the mix between journalism and entertainment. The proposal developed here goes through topics that contextualize these two areas of communication in history, which talk about a new curriculum matrix, a new dynamic between teachers and interdisciplinarity, practical training for students, the balance between theory and practice in the matrix, with practical examples from the profession and curricular matrices from international courses